2023
DOI: 10.35848/1347-4065/acac58
|View full text |Cite
|
Sign up to set email alerts
|

Total spectral power-based method for estimating Brillouin frequency shift in optical fibers

Abstract: A cost-effective method for estimating the Brillouin frequency shift (BFS) of the whole sensing fiber without using an electrical spectrum analyzer is developed. The Brillouin gain spectrum is down-converted and low-pass-filtered, and its total transmitted power is used to estimate the BFS. The strain dynamic range of this method is experimentally shown to be double the value of a conventional slope-assisted method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…1) The stimulated Brillouin laser (SBL) has the characteristics of low noise and narrow bandwidth, enabling the production of high coherent light. It has great potential in various applications such as sensing, [2][3][4][5][6] coherent optical communications 7) and microwave photonics. 8) Currently, the generation of conventional fiber Brillouin laser necessitates either a sufficiently long fiber length or a substantial input optical power, thereby posing significant challenges in achieving miniaturized SBL emission.…”
Section: Introductionmentioning
confidence: 99%
“…1) The stimulated Brillouin laser (SBL) has the characteristics of low noise and narrow bandwidth, enabling the production of high coherent light. It has great potential in various applications such as sensing, [2][3][4][5][6] coherent optical communications 7) and microwave photonics. 8) Currently, the generation of conventional fiber Brillouin laser necessitates either a sufficiently long fiber length or a substantial input optical power, thereby posing significant challenges in achieving miniaturized SBL emission.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no technique (except for the one we have developed) has been reported that enables low-cost temperature measurement near the tip of a commercially available optical fiber without necessitating any specialized processing. Alternatively, distributed sensing techniques capable of providing longitudinal temperature variations along the fiber have been explored, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but these too come with a high cost.…”
mentioning
confidence: 99%
“…Brillouin-based single-end-access distributed sensors can be categorized into three types: Brillouin optical time-domain reflectometry (BOTDR), [12][13][14] Brillouin optical frequency-domain reflectometry (BOFDR), 15) and BOCDR. [16][17][18][19][20][21][22][23][24][25][26] Each technique has its own merits and demerits, and here we focus on BOCDR.…”
mentioning
confidence: 99%
“…To solve this problem, phase-detected BOCDR 22,24) and slope-assisted (SA-) BOCDR [25][26][27][28][29][30][31] have been proposed. In particular, SA-BOCDR operates by associating power variations at a specific frequency in the sloping part of the BGS with the corresponding BFS, using the zero-span function of the ESA.…”
mentioning
confidence: 99%